2021
DOI: 10.1093/ecco-jcc/jjab215
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Oncological Outcome of Segmental Versus Extended Colectomy for Colorectal Cancer in Crohn’s Disease: Results from an International Multicentre Study

Abstract: Background and Aims Crohn’s Disease increases colorectal cancer risk, with high prevalence of synchronous and metachronous cancers. Current guidelines for colorectal cancer in Crohn’s Disease recommend pan-proctocolectomy. Aim of this study was to evaluate oncologic outcomes of a less invasive surgical approach. Methods Retrospective database analysis of Crohn’s disease patients with colorectal cancer undergoing surgery at se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We found synchronous advanced neoplasia in 3.4% of CD patients and 6.6% of UC patients treated with (sub)total or proctocolectomy. A recent Italian study in CD patients reported a higher advanced neoplasia rate of 9% after (sub)total or proctocolectomy 10 . Another observational UC study observed a higher synchronous advanced neoplasia rate of 14% 18 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We found synchronous advanced neoplasia in 3.4% of CD patients and 6.6% of UC patients treated with (sub)total or proctocolectomy. A recent Italian study in CD patients reported a higher advanced neoplasia rate of 9% after (sub)total or proctocolectomy 10 . Another observational UC study observed a higher synchronous advanced neoplasia rate of 14% 18 .…”
Section: Discussionmentioning
confidence: 94%
“…As such, one study in CD patients ( n =64) reported a cumulative metachronous CRC incidence of 40% following partial colectomy and 35% after (sub)total colectomy after median 7 years 19 . Another CD study ( n =99) reported 1.3% and 0.0% CRC rates after median 3.5 years, respectively 10 . A UC study ( n =59) did not detect any metachronous CRC after (sub)total or partial colectomy for CRC with a median follow-up of 7 years 11 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For this reason, IPAA is today the gold standard for UC patients with CAC. In Crohn's disease current guidelines recommend pan-proctocolectomy in CAC patients [41,42]. Recent studies presented that less extended resections, involving segmental colonic resections, offer similar long-term outcomes to more extensive surgery in patients with Crohn's disease and ulcerative colitis with endoscopic remission of intestinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Colorectal cancer after segmental colectomy: Reported rates of metachronous neoplasia if segmental colectomy has been performed for cancer, have varied from 0 -40% over a 7-year surveillance follow-up period with the highest incidences occurring in patients who pre-operatively had cancer rather than dysplasia 86,166,[170][171][172] . Recent studies reflecting modern surveillance and high definition endoscopic imaging practices suggest that the true synchronous rates are much lower than previously reported 4,173 .…”
Section: Risk Of Post-operative Cancermentioning
confidence: 99%